Molecular Understanding of Endothelial Cell and Blood Interactions with Bacterial Cellulose: Novel Opportunities for Artificial Blood Vessels - Fink, Helen; Sellborn, Anders; Krettek, Alexandra (IntechOpen, 2012)
None